2022
DOI: 10.1039/d2dt02438a
|View full text |Cite
|
Sign up to set email alerts
|

Solution-phase controlled synthesis of Cu3NbSe4 nanocrystals for optoelectronic applications

Abstract: Cu3MX4 (M = V, Nb, Ta; X = S, Se, Te) compounds have recently emerged as great promising solar energy conversion materials due to their tailorable band gaps, high optical...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It was found that the desired phase was still formed when oleic acid was incorporated as up to about 15% of the solvent, but the nanoparticles became irregularly shaped and non-uniform. 77 Cu 3 TaS 4 nanocubes were produced by the Radu group using dropwise hot injection of a CS 2 /dodecanethiol/oleylamine mixture into a solution of TaCl 5 and CuCl 2 in oleylamine and octadecene; they used the inverse order of injection to prepare Cu 3 TaSe 4 nanoparticles by rapidly injecting a TaCl 5 /CuCl 2 /oleylamine/octadecene precursor mixture into a solution of elemental selenium in oleylamine/octadecene that had been heated to 300 °C. 73 The Cu 3 TaSe 4 particles had a poorly defined core–shell-like morphology.…”
Section: Synthesis Of Early Transition Metal Chalcogenide Nanomaterialsmentioning
confidence: 99%
“…It was found that the desired phase was still formed when oleic acid was incorporated as up to about 15% of the solvent, but the nanoparticles became irregularly shaped and non-uniform. 77 Cu 3 TaS 4 nanocubes were produced by the Radu group using dropwise hot injection of a CS 2 /dodecanethiol/oleylamine mixture into a solution of TaCl 5 and CuCl 2 in oleylamine and octadecene; they used the inverse order of injection to prepare Cu 3 TaSe 4 nanoparticles by rapidly injecting a TaCl 5 /CuCl 2 /oleylamine/octadecene precursor mixture into a solution of elemental selenium in oleylamine/octadecene that had been heated to 300 °C. 73 The Cu 3 TaSe 4 particles had a poorly defined core–shell-like morphology.…”
Section: Synthesis Of Early Transition Metal Chalcogenide Nanomaterialsmentioning
confidence: 99%
“…Zhao et al reported the synthesis of cube-shaped Cu 3 NbSe 4 nanocrystals with high crystallinity, uniformity, and monodispersity using a facile method. It demonstrates the optoelectronic properties of Cu 3 NbSe 4 , showing its potential for application in electronics and optoelectronics, particularly as a photoactive material with a higher light-to-dark current ratio ( I light / I dark ) representing strong sensitivity toward incident light giving broad spectral light-harvesting ability, fast response speeds, and excellent stability . We successfully demonstrated the ability to fine-tune the Cu 3 VSe 4 nanocrystal particle size in the range of ∼25 to 30 nm by tailoring the amount of surfactant utilized in the synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It demonstrates the optoelectronic properties of Cu 3 NbSe 4 , showing its potential for application in electronics and optoelectronics, particularly as a photoactive material with a higher light-to-dark current ratio (I light / I dark ) representing strong sensitivity toward incident light giving broad spectral light-harvesting ability, fast response speeds, and excellent stability. 29 We successfully demonstrated the ability to finetune the Cu 3 VSe 4 nanocrystal particle size in the range of ∼25 to 30 nm by tailoring the amount of surfactant utilized in the synthesis. While absorbance is in the UV−visible region of the solar spectrum, the particle size impacts the Cu 3 VSe 4 -specific absorbance wavelength, enabling the rational design of particles with desired optical properties.…”
Section: ■ Introductionmentioning
confidence: 99%